2011
DOI: 10.1021/jp202401b
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid G-quartets: Insights into Diverse Patterns and Optical Properties

Abstract: We thank DST À Fast Track scheme, CSIR, and University Grants Commission (UGC) for partial funding. We thank Prof. M. Hariharan for fruitful discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 147 publications
5
71
1
Order By: Relevance
“…It should be mentioned that dispersion interactions play a major role in the stabilities of large biomolecules, such as DNA, in which these interactions are abundant. For example, Datta and coworkers investigated the nucleic acid G‐quartets38 and various conformations of different DNA‐base mispairs39 and found that dispersion interactions play an important role in the stabilities of the studied complexes. Therefore, it could be anticipated that dispersion interactions also have influences on the stabilities of the base pairs studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that dispersion interactions play a major role in the stabilities of large biomolecules, such as DNA, in which these interactions are abundant. For example, Datta and coworkers investigated the nucleic acid G‐quartets38 and various conformations of different DNA‐base mispairs39 and found that dispersion interactions play an important role in the stabilities of the studied complexes. Therefore, it could be anticipated that dispersion interactions also have influences on the stabilities of the base pairs studied in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Close proximity of Truhlar's M06-2X meta-GGA-hybrid functional with benchmark databases has been previously reported in literature for a wide variety of molecular complexes. 13,14 According to previous benchmarks we expect the M06-2X and ωB97XD functional to give the most accurate DFT binding energies. 15,16 For the ONIOM calculations, the high layer consisting of the UBP along with the linked sugars and phosphates was performed at the M06-2X/6-31+(d) level, while the low layer consisting of the four natural base pairs above and below the UBP inclusive of their link sugars and phosphates was performed at the semiempirical PM3 level.…”
Section: ■ Computational Detailsmentioning
confidence: 94%
“…For geometry optimization and subsequent interaction energy calculations, we have selected Truhlar's M05-2X 39 functional and the 6-31G++(2d,2p) basis set 40 . M05-2X is a hybrid meta GGA functional with 56% Hartree-Fock exchange component and is known to perform remarkably well for noncovalently bonded molecules of biological relevance, 41 including nucleobases [42][43][44][45][46][47][48][49] . 6-31G++(2d,2p) is a split valance double ζ type basis set, with two sets of d type polarization function for all non-hydrogen atoms and two sets of p type polarization function for hydrogen atoms, and also include s-p diffused orbitals for non-hydrogen atoms, was used for ground state geometry optimization.…”
Section: Tools and Methodsmentioning
confidence: 99%